Consuming Boiled Red Ginger Water Can Reduce Dysmenorrhea in Adolescent Girls: Konsumsi Air Rebusan Jahe Merah dapat Mengurangi Dismenorea pada Remaja Putri - Batadi, Nur Azizah; Sumiaty; Tondong, Henrietta Imelda; Muliani; Lisnawati; Narmin (Poltekkes Kemenkes Palu, 2025)
Background: Menstrual pain, or dysmenorrhea, must be treated because it interferes with the comfort of adolescent girls and can affect their learning process. In addition to the use of drugs, menstrual pain can be treated with non-pharmacological methods. Objective: To determine the effect of red ginger boiled water on dysmenorrhea in adolescent girls who work at the Sangurara Health Center. Method: The research design was pre-experimental with a control group pretest - posttest design. Respondents totaling 32 adolescent girls were taken by total sampling, divided into 16 people each in the control and intervention groups. Data analysis used the Marginal Homogeneity test. Results: Before the treatment, all of the control and intervention groups had moderate menstrual pain, while after that, as many as (62.5%) of the intervention group experienced mild pain and the control remained on a moderate scale. The results of the data analysis asymp. Sig value: 0.000, so Ho is rejected. Conclusion: Giving red ginger boiled water can reduce dysmenorrhea in adolescent girls at the Sangurara Health Center. It is better to consume red ginger boiled water for adolescent girls to reduce abdominal pain during menstruation.